Langka Lipu: Warisan Budaya dan Identitas Masyarakat Adat Banggai - Ahmad, B.; Nasrum, Muh.; Aepu, Siti Hajar; Badollahi, Muh. Zainuddin (CV. Social Politic Genius (SIGn), 2022)
This research aims to understand the philosophy of movements and the values embodied in Langka Lipu and to explore how this martial art has managed to survive. This research uses an ethnographic analysis. Ethnographic analysis is an approach that begins with field facts, analyzes them based on cultural theories and relevant arguments to explore the cultural situation of the community, and ultimately yields a conclusion. The results show that Langka Lipu, as a cultural heritage of the Banggai tribe, is more than just a martial arts practice; it is a profound philosophical expression. Religious values are integrated into every aspect of Langka Lipu, making it a means for spiritual and personal development. The educational values transmitted through the teacher-student relationship emphasize character formation and good social values. The cultural transmission process of Langka Lipu, demonstrates a structured strategy to preserve and disseminate this martial art. Thus, Langka Lipu is successfully preserved as a valuable cultural heritage and a crucial pillar of the Banggai indigenous people’s identity. Therefore, it is recommended that practitioners continue to explore and practice the religious and educational values contained in Langka Lipu to enrich and deepen the spiritual and social meanings of this cultural heritage. The Department of Tourism and Culture of Banggai Laut Regency is expected to increase support and recognition for Langka Lipu by integrating it into cultural development and tourism programs aimed at promoting and preserving the original cultural heritage of the Banggai tribe. For the Banggai indigenous people, it is crucial to continue actively participating in the cultural transmission process of Langka Lipu, whether through targeting potential teenagers, socializing values and philosophy, conducting regular training, or in efforts to increase the number of school branches, thus ensuring that the core values and essence of Langka Lipu continue to live and thrive within the community.